Influence of Pupils Interpretation of Kenyan Sign Language on Academic Performance of Pupils with Hearing Impairment in Selected Public Primary Schools, Kenya - and M Wawire, Tom; Namunga, Nick (2019)
The government of Kenya recognizes the importance of special needs education as a crucial sector for accelerating the attainment of Education for all students and the 2030 Millennium Development Goals. The purpose of this study was to establish the relationship between mastery of Kenya Sign Language (KSL) and academic performance of pupils with hearing impairment in public primary schools in western Kenya. Study objective was to find out the influence of pupils’ interpretation of Kenya Sign Language on academic performance. The study employed a mixed research approach and a descriptive survey design to collect qualitative and quantitative data. Using purposive sampling technique, 12 head teachers, 93 teachers and 108 pupils with hearing impairment forming a sample size of 213 respondents. Research instruments used were a Likert scale questionnaire and interview schedule. Piloting of the questionnaire was done in a public special primary school for the pupils with hearing impairment in Birunda School for the Deaf in Trans Nzoia. The collected data was analysed using descriptive statistics of frequencies, percentages, means, standard deviation and Pearson correlation coefficient and inferential statistics of chi-square using the statistical package for social sciences [SPSS] program of version 23. Qualitative data was analysed by describing the emerging themes in relation to the study objectives. The study established that there was significant relationship between pupils’ interpretation of KSL at p<0.05. Therefore, the null hypothesis was rejected and concluded that mastery of KSL significantly influences academic performance. The results will help stakeholders in the education sector to establish how KSL is used in the teaching of pupils with hearing impairment in schools, hence providing valuable data on the current policy and practice in the field of education and training of teachers of the learners with hearing impairment. The following recommendations were made: pupils should be equipped with more interpretation and literacy skills for the KSL, further training in special needs education be given to teachers and adequate resources and support services be given to the learners.